Goat-crop-fodder integrated farming system at village level - CERBITO, W A; VILLAR, E C; SATO, K; QUERO (JR), F; BALAGAPO(JR), C R; FAYLON, P S (The Indian Journal of Animal Sciences, 2013)
An on-farm trial was conducted to demonstrate and verify through a dispersal strategy the technical viability, economic feasibility and social acceptability of integrating goat into farming system under improved management. Three levels of animal holding of 2,4 and 6 breedable goats were distributed across farms to determine the economic and optimum size of herd that will yield maximum retums. Increasing percentage of Anglo-Nubian blood in natives resulted in increased birth weights. Mortality in pre-weaning and growing kids (21.1 %) was higher than for in adults (18.5%). Goal raising contributed18.8-25.7% extra income to farmers depending on the level of animal holding. Two (2) and 6 head levels of goats were considered minimum and of optimum economic size respectively. The role of family members, especially children, for the care and management of goats was recognized. Goat management practices and options of farmers were documented.